Konstruksi Kepercayaan Diri Korban Cyberbullying di Media Sosial Instagram - Citra Puspa Maulidina; Annasyha Fitriani; Widiastiana Vista Wijaya; Shilvy Andini Sunarto; Nadinta Rafifah Suaib (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to find out if there is an impact of Cyberbullying on Instragram Social Media on the self-confidence of Gunadarma University students Batch 2020. This research is a library research with a qualitative descriptive approach. The data collection technique was in the form of interviews from several students at Gunadarma University Class of 2020. Cyberbullying is bullying using digital technology. This can happen on social media, chat platforms, gaming platforms, and mobile phones. The results of research that has been conducted through interviews with several informants can be concluded that the impact of Cyberbullying behavior on Instagram social media results that the interaction between the perpetrator and the victim disturbs the victim's mind. On Instagram social media, this is still recognized by victims as Cyberbullying and victims choose to deal with it on their own without telling those closest to them, because there is no self-defense, then Cyberbullying will continue to develop in social life. Even the phenomenon of Cyberbullying is considered normal by some people due to the lack of application of laws governing Cyberbullying. Keywords: Cyberbullying, New Media, Instagram